Texture Synthesis Based Thyroid Nodule Detection From Medical Ultrasound Images: Interpreting and Suppressing the Adversarial Effect of In-place Manual Annotation - Yao, Siqiong; Yan, Junchi; Wu, Mingyu; Yang, Xue; Zhang, Weituo; Lu, Hui; Qian, Biyun (Frontiers in Bioengineering and Biotechnology, 2020)
Deep learning method have been offering promising solutions for medical image processing, but failing to understand what features in the input image are captured and whether certain artifacts are mistakenly included in the model, thus create crucial problems in generalizability of the model. We targeted a common issue of this kind caused by manual annotations appeared in medical image. These annotations are usually made by the doctors at the spot of medical interest and have adversarial effect on many computer vision AI tasks. We developed an inpainting algorithm to remove the annotations and recover the original images.Besides we applied variational information bottleneck method in order to filter out the unwanted features and enhance the robustness of the model.Our impaiting algorithm is extensively tested in object detection in thyroid ultrasound image data.The mAP (mean average precision, with IoU=0.3) is 27% without the annotation removal. The mAP is 83% if manually removed the annotations using Photoshop and is enhanced to 90% using our inpainting algorithm. Our work can be utilized in future development and evaluation of artificial intelligence models based on medical images with defects.